TVA, Abnormal Return, and Investor Perception on Changing of Tick Size 2 May 2016 - Tri Gunarsih; Astri Wening Perwitasari (University of Merdeka Malang, 2017)
The objective of this study was to analyze the market reaction to the changing of the capital market's tick size regulation on May 2, 2016. The main goal of the regulation was to increase the capital market liquidity, then it’s important to test whether there was a difference in market liquidity before and after the regulation released. The method of this study was studying with Trading Volume Activity (TVA) and abnormal return based on secondary data and also investor perception based on primary data. The secondary data consist of 65 samples of listed companies in Indonesia Stock Exchange. The primary data consist of 67 investors in Yogyakarta that were selected using a purposive sampling method. The result of this study was a mix, there was no difference before and after the release of regulation in TVA, but there was a difference in abnormal return. The result of investor perception shows that there was a positive response to the changing of tick size regulation.